Shear thinning and local melting of colloidal crystals. - Dullens, R; Bechinger, C (2011)
Phenomena such as shear thinning and thickening, occurring when complex materials are exposed to external forces, are generally believed to be closely connected to changes in the microstructure. Here, we establish a direct and quantitative relation between shear thinning in a colloidal crystal and the surface area of the locally melted region by dragging a probe particle through the crystal using optical tweezing. We show that shear thinning originates from the nonlinear dependence of the locally melted surface area on the drag velocity. Our observations provide unprecedented quantitative evidence for the intimate relation between mechanical properties and underlying changes in microscopic structure.